Peran Konseling Pastoral dalam Kemandirian Anak Berkebutuhan Khusus di Rumah Pengharapan Baru Bandung Barat - Meyshi Mutangoan (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to explore the Role of Pastoral Counseling in the Independence of Children with Special Needs at Rumah Pengharapan Baru (RPB) West Bandung. Qualitative methods were used to collect data through in-depth interviews, participant observation, and document analysis, involving pastoral counselors, Rumah Pengharapan Baru staff, and children with special needs. The results of the study indicate that pastoral counseling plays a significant role in increasing the independence of children with special needs, covering emotional, spiritual, and social aspects that support the development of independent living skills. Pastoral counselors function as companions and facilitators who help children understand and accept their condition, build self-confidence, and motivate them to achieve their maximum potential. A holistic and personal counseling approach and ongoing support from the Rumah Pengharapan Baru environment are effective in strengthening the independence of these children. This study concludes that children with special needs need intensive assistance and holistic care. Pastoral counseling plays an important role in providing emotional and spiritual support, helping them overcome anxiety and low self-esteem. Professional counselors who are caring and compassionate are the foundation of this ministry, ensuring that the emotional, psychological, and spiritual needs of children are met in a balanced manner.